2021
DOI: 10.1002/ca.23717
|View full text |Cite
|
Sign up to set email alerts
|

The glenohumeral ligaments: Superior, middle, and inferior: Anatomy, biomechanics, injury, and diagnosis

Abstract: The three glenohumeral ligaments (superior, middle, and inferior) are discrete thickenings of the glenohumeral joint capsule and are critical to shoulder stability and function. Injuries to this area are a cause of significant musculoskeletal morbidity. A literature search was performed by a review of PubMed, Google Scholar, and OVID for all relevant articles published up until 2020. This study highlights the anatomy, biomechanical function, and injury patterns of the glenohumeral ligaments, which may be relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 149 publications
(212 reference statements)
0
4
0
Order By: Relevance
“…The higher stress of the posterior deltoid muscle may be due to the increase in load changed the motion trajectory, which caused an increase in stress. In addition, the glenohumeral ligament is a statically stable structure of the shoulder joint and is one of the main stabilizing factors of the shoulder during abduction 32 . The finite element model showed that the tensile strain of IGHL is the most obvious with increasing abrasion and load, which is more likely to cause tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…The higher stress of the posterior deltoid muscle may be due to the increase in load changed the motion trajectory, which caused an increase in stress. In addition, the glenohumeral ligament is a statically stable structure of the shoulder joint and is one of the main stabilizing factors of the shoulder during abduction 32 . The finite element model showed that the tensile strain of IGHL is the most obvious with increasing abrasion and load, which is more likely to cause tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, specific zones of the capsule are reinforced by extrinsic and intrinsic ligaments that contribute to the stabilization of the shoulder. The superior, middle, and inferior glenohumeral ligaments are rather inconstant and highly variable thickenings of the capsule that are best observed from the inner side of the joint cavity during arthroscopic procedures [15]. There is an ongoing debate about the exact anatomy of the glenohumeral ligaments, which is, however, beyond the scope of this work.…”
Section: Relevant Anatomymentioning
confidence: 95%
“…In its most typical appearance, the middle glenohumeral ligament originates from the supraglenoid tubercle in close contiguity to the superior glenohumeral ligament and inserts in the humeral neck just medial to the lesser tuberosity or into the deep surface of the subscapularis tendon [17]. The inferior glenohumeral ligament has been reported in between 72% and 93% of subjects [15,18]. When present, the ligament has a hammock-like shape and is constituted by a constant anterior band arising from the anteroinferior aspect of the glenoid labrum between 3 and 5 o'clock and an inconstant posterior band, which can be observed in 41-73% of cases and arises from the posteroinferior aspect of the glenoid labrum between 7 and 9 o'clock.…”
Section: Relevant Anatomymentioning
confidence: 99%
“…Of all joints in the human body, the shoulder joint is the most mobile, due to its unique anatomical structure: the articular surface of the humeral head is indeed three times larger than the articular surface of the acetabulum, allowing for a wider range of movement [9]. Joint stabilizers (both static and dynamic) further impact the joint's mobility, affecting the entire upper limb's ability to grasp and manipulate objects with adequate efficiency [10]. On the other side, this high mobility is also responsible for the increased predisposition to dislocations.…”
Section: Introductionmentioning
confidence: 99%